2021
DOI: 10.1098/rsfs.2021.0018
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic drugs at pandemic speed: infrastructure for accelerating COVID-19 drug discovery with hybrid machine learning- and physics-based simulations on high-performance computers

Abstract: The race to meet the challenges of the global pandemic has served as a reminder that the existing drug discovery process is expensive, inefficient and slow. There is a major bottleneck screening the vast number of potential small molecules to shortlist lead compounds for antiviral drug development. New opportunities to accelerate drug discovery lie at the interface between machine learning methods, in this case, developed for linear accelerators, and physics-based methods. The two in silico … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Top scoring 187 hits (75 FDA-approved) were further validated by all atom docking studies, and important molecular descriptors and promising chemical fragments are identified to guide future experiments. Coveney et al designed a novel in silico method for drug design by coupling ML with physics-based (PB) simulations ( Bhati et al, 2021 ). The accurate PB simulations would make the drug design process smarter by calculating the binding free energies of obtained hits from the output of a deep learning (DL) algorithm, which will then fed back to the DL algorithm to improve its predictive performance.…”
Section: Targets For Novel Drug Developmentmentioning
confidence: 99%
“…Top scoring 187 hits (75 FDA-approved) were further validated by all atom docking studies, and important molecular descriptors and promising chemical fragments are identified to guide future experiments. Coveney et al designed a novel in silico method for drug design by coupling ML with physics-based (PB) simulations ( Bhati et al, 2021 ). The accurate PB simulations would make the drug design process smarter by calculating the binding free energies of obtained hits from the output of a deep learning (DL) algorithm, which will then fed back to the DL algorithm to improve its predictive performance.…”
Section: Targets For Novel Drug Developmentmentioning
confidence: 99%
“…Clear evidence of non-Gaussian distributions typically requires substantial data sets 9 and thus ensembles of much larger size than the ones we recommend for routine (non-corner-cutting) uncertainty quantification, namely with 25 replicas in ESMACS and 5 for TIES. We have used both relaxed and full ensemble protocols in our IMPECCABLE workflow as filters to perform screening at different stages with different levels of precision 10 . Such relaxed protocols are termed as "coarse-grained (CG)" against the full protocol that is termed as "fine-grained (FG)".…”
Section: General Rules Of Thumb For "Cutting Corners" During Large-sc...mentioning
confidence: 99%
“… 11 Moreover, these calculations can allow much larger areas of chemical space to be explored than would be possible experimentally. Compounds drawn from this chemical space can be selected from numerous sources such as chemical libraries, 12 repurposing of approved drugs, 13 generative AI methods, 14 16 or even other free energy calculations. 17 …”
Section: Introductionmentioning
confidence: 99%